’n Teologies-pastorale ondersoek na die sosio-ekonomiese situasie van die bruin welsynpensioenarisse in die Redeemed African Metodiste Kerk - Carnow, Jacobus; Thesnaar, Christo (Stellenbosch Theological Journal, 2018)
A theologically-pastoral examination of the socio-economic situation of the brown welfare pensioners in the Redeemed African Methodist Church The South African society is characterised by socio-economic inequality between various social components which is also reflected in the older persons' population (Beukes 2014:32). The objective of this article is a theological-pastoral investigation of how apartheid and neoliberal market economy could be structurally responsible for the socio-economic situation of brown welfare pensioners which is then interpreted in the light of God's justice. The insight gained could then be used by the Redeemed African Methodist Church to devise an appropriate theological-pastoral strategy to assist these older persons. This article is based on empirical data that was gathered by means of focus group methodology. The findings are that these older persons are victims of external factors determining their socio-economic situation. The theoretical framework of this article is that theological-pastoral care to these older persons cannot be separated from theological-pastoral care of the public life.